2012
DOI: 10.1186/1756-0500-5-697
|View full text |Cite
|
Sign up to set email alerts
|

The impact of voluntary exercise on relative telomere length in a rat model of developmental stress

Abstract: BackgroundExposure to early adverse events can result in the development of later psychopathology, and is often associated with cognitive impairment. This may be due to accelerated cell aging, which can be catalogued by attritioned telomeres. Exercise enhances neurogenesis and has been proposed to buffer the effect of psychological stress on telomere length. This study aimed to investigate the impact of early developmental stress and voluntary exercise on telomere length in the ventral hippocampus (VH) and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 51 publications
1
14
1
2
Order By: Relevance
“…In addition, the LBN environment had consequences for brain telomere length that differ between males and females (Arun Asok, Bernard, Rosen, Dozier, & Roth, 2014; A Asok, Bernard, Roth, Rosen, & Dozier, 2013). Telomere length is another biomarker of stress emerging as highly sensitive to variations in the caregiving environment (Botha et al, 2012; Drury et al, 2012; Tyrka et al, 2010). …”
Section: Sex Differences In Outcomesmentioning
confidence: 99%
“…In addition, the LBN environment had consequences for brain telomere length that differ between males and females (Arun Asok, Bernard, Rosen, Dozier, & Roth, 2014; A Asok, Bernard, Roth, Rosen, & Dozier, 2013). Telomere length is another biomarker of stress emerging as highly sensitive to variations in the caregiving environment (Botha et al, 2012; Drury et al, 2012; Tyrka et al, 2010). …”
Section: Sex Differences In Outcomesmentioning
confidence: 99%
“…The role of exercise intensity has not being analyzed properly in the few studies investigating the effects of chronic exercise on telomere biology. Usually the studies have used voluntary wheel running as intervention, or individuals already adapted to exercise (cross-sectional studies) or individuals performing intervention at only one exercise intensity [5,40,47]. In this sense, the determination of lactate threshold (LT) has been used as a tool to distinguish limits of metabolic domains during exercise in humans and rodents, such that exercise intensity is considered moderate below the LT and of high-intensity above the LT [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Rats selectively bred for enhanced depressive‐like symptoms (i.e., the Flinders‐sensitive line) show reduced telomere length in the hippocampus (Wei et al, 2015), supporting a role for telomere shortening in the brain. In contrast, other studies have found that postnatal stress (e.g., maternal separation or caregiver maltreatment) is associated with longer telomeres in the ventral hippocampus and medial prefrontal cortex (Asok et al, 2014; Botha et al, 2012). The findings here complement our previous work with regard to stress effects on a common brain region (i.e., the mPFC), but differ in the direction of telomere change.…”
Section: Discussionmentioning
confidence: 83%